A mountain of millipedes IV: Species of Prionopetalum Attems, 1909 from the Udzungwa Mountains, Tanzania. With notes on "P." fasciatum (Attems, 1896) and a revised species key (Diplopoda, Spirostreptida, Odontopygidae) - Enghoff, Henrik (European Journal of Taxonomy, 2016)
Two species of the genus Prionopetalum Attems, 1909, are recorded from the Udzungwa Mountains: P. asperginis sp. nov. and P. kraepelini (Attems, 1896). Prionopetalum stuhlmanni Attems, 1914 is synonymized under P. kraepelini. Odontopyge fasciata Attems, 1896, is transferred from Prionopetalum to Aquattuor Frederiksen, 2013, and new illustrations are given. A new illustrated key to species of Prionopetalum is provided.